2016
DOI: 10.2147/copd.s109510
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic assessment of pulmonary hypertension using high-resolution echocardiography is feasible in neonatal mice with experimental bronchopulmonary dysplasia and pulmonary hypertension: a step toward preventing chronic obstructive pulmonary disease

Abstract: Bronchopulmonary dysplasia (BPD) and chronic obstructive pulmonary disease (COPD) are chronic lung diseases of human infants and adults, respectively, that are characterized by alveolar simplification. One-third of the infants with severe BPD develop pulmonary hypertension (PH). More importantly, PH increases morbidity and mortality in BPD patients. Additionally, COPD is a common respiratory morbidity in former BPD patients. The lack of an appropriate small animal model wherein echocardiography (Echo) can demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Hyperoxia impairs signaling pathways necessary for lung development and repair [43,44], disrupts alveolarization and pulmonary vascularization in preterm infants [45] and newborn mice [46], and causes BPD. Furthermore, our hyperoxia model is shown to recapitulate the short-and long-term phenotype of BPD infants with PH [33,34]. Consistent with this notion, our hyperoxia-exposed animals displayed alveolar and pulmonary vascular simplification.…”
Section: Discussionsupporting
confidence: 83%
“…Hyperoxia impairs signaling pathways necessary for lung development and repair [43,44], disrupts alveolarization and pulmonary vascularization in preterm infants [45] and newborn mice [46], and causes BPD. Furthermore, our hyperoxia model is shown to recapitulate the short-and long-term phenotype of BPD infants with PH [33,34]. Consistent with this notion, our hyperoxia-exposed animals displayed alveolar and pulmonary vascular simplification.…”
Section: Discussionsupporting
confidence: 83%
“…In alignment with other studies [5, 6], we recently demonstrated that hyperoxia-induced lung parenchymal and vascular injury in newborn mice leads to a phenotype that is similar to human BPD [7]. So, we used this model to investigate whether AM signaling is disrupted in experimental BPD.…”
Section: Introductionmentioning
confidence: 64%
“…We demonstrated that our mouse model of hyperoxia-induced lung injury meets the requirements needed to model BPD with pulmonary hypertension (PH) experimentally [7]. In that study, we observed that hyperoxia exposure disrupted lung development in mice at PND 14.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations